Electroactive materials for metal-ion batteries

By using porous carbon skeleton and nano-sized element silicon in the anode of lithium-ion battery, the large volume changes and mechanical stress problems of silicon materials in the charging-discharge cycle are solved, and high capacity and high reversible capacity retention rates are achieved. Effect.

CN113330599BActive Publication Date: 2025-02-25NEXEON LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201980088762.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-09
Filing Date
2019-12-19
Publication Date
2025-02-25
Estimated Expiration
2039-12-19

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the use of silicon as anode material is complicated by large volume changes during charging and discharging, resulting in mechanical stress, electrical contact loss and instability of the solid electrolyte interface layer, which in turn leads to unacceptable electrochemical capacity. loss.

Method used

By providing particulate materials containing porous carbon skeletons and nano-sized element silicon domains located within the pores of the porous carbon skeleton, the pore structure of the porous carbon skeleton and the available pore volume ratio of the silicon to porous carbon skeletons for optimal performance .

Benefits of technology

The effect of combining high lithiation capacity with capacity retention and structural stability during multiple charge-discharge cycles is achieved, and structural rupture and capacity loss of silicon materials in the charge-discharge cycle is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113330599B_ABST
    Figure CN113330599B_ABST
Patent Text Reader

Abstract

The present invention relates to a particulate material comprising a plurality of composite particles, wherein the composite particles comprise: (a) a porous carbon skeleton comprising micropores and mesopores, wherein the total pore volume of the micropores and mesopores is at least 0.6 cm 3 / g, wherein the volume fraction of micropores is in the range of 0.1 to 0.9, and the volume fraction of pores with a pore diameter of no more than 20 nm is at least 0.75, and the D 50 The particle size is less than 20 μm; (b) a defined amount of silicon located in the micropores and / or mesopores of the porous carbon framework relative to the micropore and / or mesopore volume.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to electroactive materials suitable for use in electrodes of rechargeable metal ion batteries, and more particularly to particulate materials having high electrochemical capacity suitable for use as anode active materials in rechargeable metal ion batteries. The particulate electroactive materials of the present invention have particular utility in hybrid anodes comprising two or more different electroactive materials. Background Art

[0002] Rechargeable metal ion batteries are widely used in portable electronic devices, such as mobile phones and laptops, and are increasingly used in electric vehicles or hybrid vehicles. Rechargeable metal ion batteries generally include an anode layer, a cathode layer, an electrolyte for transporting metal ions between the anode layer and the cathode layer, and an electrically insulating porous separator disposed between the anode and the cathode. The cathode generally includes a metal current collector having a metal oxide composite material layer containing metal particles, and the anode generally includes a metal current collector having an electroactive material layer, which is defined herein as a material capable of embedding and releasing metal ions during charging and discharging of the battery. To avoid doubt, the terms "cathode" and "anode" are used herein in the following sense: the battery is connected to a load so that the cathode is the positive electrode and the anode is the negative electrode. When the metal ion battery is charged, the metal ions are transported from the cathode layer containing the metal ions to the anode via the electrolyte and are embedded in the anode material. The term "battery" herein refers to both a device containing a single anode and a single cathode and a device containing multiple anodes and / or multiple cathodes.

[0003] There is interest in improving the gravimetric and / or volumetric capacity of rechargeable metal ion batteries. The use of lithium ion batteries has provided substantial improvements when compared to other battery technologies, but there is still room for further development. To date, commercial lithium ion batteries have been largely limited by the use of graphite as the anode active material. When the graphite anode is charged, lithium is intercalated between the graphite layers to form a lithium ion battery with the empirical formula Li x C6 (where x is greater than 0 and less than or equal to 1). Thus, the maximum theoretical capacity of graphite in lithium-ion batteries is 372 mAh / g, with actual capacities slightly lower (approximately 340 to 360 mAh / g). Other materials such as silicon, tin, and germanium can intercalate lithium at significantly higher capacities than graphite, but have not been widely used commercially due to difficulties in maintaining sufficient capacity over multiple charge / discharge cycles.

[0004] In particular, silicon is considered a promising graphite substitute for making rechargeable metal ion batteries with high weight and volumetric capacity due to its very high lithium capacity (see, for example, Insertion Electrode Materials for rechargeable Lithium Batteries, Winter, M et al., Adv. Mater. 1998, 10, No. 10). At room temperature, the theoretical maximum specific capacity of silicon in lithium ion batteries is about 3,600 mAh / g (based on Li 15 However, the use of silicon as an anode material is complicated by the large volume change during charge and discharge.

[0005] The insertion of lithium into bulk silicon results in a substantial increase in the volume of the silicon material, up to 400% of its original volume when silicon is lithiated to its maximum capacity, and repeated charge-discharge cycles induce significant mechanical stresses in the silicon material, leading to fracture and delamination of the silicon anode material. The volume shrinkage of silicon particles during delithiation may result in loss of electrical contact between the anode material and the current collector. Another difficulty is that the solid electrolyte interface (SEI) layer formed on the silicon surface does not have sufficient mechanical tolerance to accommodate the expansion and contraction of silicon. As a result, the newly exposed silicon surface leads to further electrolyte decomposition and increased SEI layer thickness as well as irreversible lithium consumption. These damage mechanisms together lead to unacceptable electrochemical capacity loss during continuous charge and discharge cycles.

[0006] A variety of approaches have been proposed to overcome the problems associated with the volume changes observed when silicon-containing anodes are charged. The most common approach to addressing the irreversible capacity loss of silicon-containing anodes is to use some form of finely structured silicon as the electroactive material. Fine silicon structures such as silicon films and silicon nanoparticles with cross-sections below about 150 nm have been reported to be more tolerant of volume changes during charge and discharge than silicon particles in the micrometer size range. However, none of them are particularly suitable for commercial-scale applications in their unmodified form; nanosized particles are difficult to prepare and handle, and silicon films do not provide sufficient bulk capacity. For example, nanosized particles tend to form agglomerates, making it difficult to obtain a usable dispersion of particles within the anode material matrix. In addition, the formation of agglomerates of nanosized particles leads to unacceptable capacity losses upon repeated charge-discharge cycles.

[0007] Ohara et al. (Journal of Power Sources 136 (2004) 303-306) have described the evaporation of silicon as a thin film onto a nickel foil current collector and the use of this structure as an anode for a lithium ion battery. Although this method gave good capacity retention, the thin film structure did not give a usable amount of capacity per unit area, and any improvement was eliminated as the film thickness increased.

[0008] WO 2007 / 083155 discloses that improved capacity retention can be obtained by using silicon particles having a high aspect ratio (ie the ratio of the largest dimension to the smallest dimension of the particle).

[0009] It is also generally known that electroactive materials such as silicon can be deposited in the pores of porous support materials such as activated carbon materials. These composite materials provide some beneficial charge-discharge properties of nanosized silicon particles while avoiding the difficulty of handling nanoparticles. For example, Guo et al. (Journal of Materials Chemistry A, 2013, pp. 14075-14079) disclose a silicon-carbon composite material in which a porous carbon substrate provides a conductive skeleton and silicon nanoparticles are deposited in a uniformly distributed pore structure of the substrate. SEI formation during the initial charge cycle is limited by the remaining pore volume, so that the remaining silicon is not exposed to the electrolyte in subsequent charge cycles. It is known that the composite material has an improved capacity retention rate over multiple charge cycles, but the initial capacity of the composite material (in mAh / g) is significantly lower than the initial capacity of the silicon nanoparticles.

[0010] JP2003100284 discloses an active material comprising a carbon-based scaffold with small pores branching from some larger pores. The electroactive material (eg silicon) is randomly located on the walls of both the large and small pores, as well as on the outer surface of the carbon-based scaffold.

[0011] Despite the efforts made to date, there is a continuing need to improve the electrochemical storage capacity of lithium-ion batteries. While one long-term goal is to develop electrodes containing a high proportion of silicon as the electroactive material, another goal of battery manufacturers is to determine ways to supplement the capacity of graphite anodes using small amounts of silicon. Therefore, the current focus is on obtaining incremental improvements to existing metal-ion battery technology by using "hybrid" electrodes containing a combination of graphite and Si-based electroactive materials rather than a wholesale transition from graphite anodes to silicon anodes.

[0012] The use of hybrid electrodes brings its own challenges. Any additional electroactive material must be provided in a form that is compatible with the graphite particle form used in the metal ion battery. For example, the additional electroactive material must be dispersed throughout the graphite particle matrix, and the particles of the additional electroactive material must have sufficient structural integrity to survive mixing with the graphite particles and subsequent electrode layer formation (e.g., by steps such as compression, drying, and calendering).

[0013] In addition, when developing hybrid anodes, differences in the metallization properties of graphite and other electroactive materials must be considered. For example, in the lithiation of a silicon-graphite hybrid anode in which graphite accounts for at least 50% by weight of the electroactive material, the silicon needs to be lithiated to its maximum capacity to obtain the capacity benefits from all electroactive materials. While in non-hybrid silicon electrodes, the silicon material will typically be limited to approximately 25 to 60% of its maximum weight capacity during charge and discharge to avoid excessive mechanical stress on the silicon material and resulting in a reduction in the overall volumetric capacity of the battery, this option is not available for hybrid electrodes. Therefore, the silicon material must be able to withstand very high levels of mechanical stress during repeated charge and discharge cycles. Summary of the invention

[0014] Therefore, there is a need in the art for silicon-containing electroactive materials that combine high lithiation capacity with adequate capacity retention and structural stability over multiple charge-discharge cycles. In particular, materials such as graphite used to supplement conventional electroactive materials will need to maintain capacity and structural stability when repeatedly lithiated to their maximum capacity. The present invention solves this problem by providing a particulate material comprising a porous carbon framework and a plurality of nano-sized elemental silicon domains located within the pores of the porous carbon framework. The pore structure of the porous carbon framework and the ratio of silicon to the available pore volume of the porous carbon framework are carefully controlled to obtain optimal performance, particularly under the stringent standards required for hybrid electrodes.

[0015] In a first aspect, the present invention provides a particulate material comprising a plurality of composite particles, wherein the composite particles comprise:

[0016] (a) A porous carbon framework comprising micropores and mesopores, wherein

[0017] (i) wherein the total pore volume of the micropores and mesopores measured by gas adsorption is P1cm 3 / g, where the value of P1 is at least 0.6,

[0018] (ii) The volume fraction of micropores based on the total volume of micropores and mesopores In the range of 0.1 to 0.9

[0019] within the enclosure;

[0020] (iii) Volume fraction of pores with a pore size of 20 nm or less based on the total volume of micropores and mesopores is at least 0.75, and

[0021] (iv) D of the porous carbon skeleton 50 Particle size less than 20 μm;

[0022] (b) a plurality of nano-sized domains of elemental silicon located within the micropores and / or mesopores of the porous carbon framework;

[0023] The weight ratio of silicon in the composite particles to the porous carbon skeleton is in the range of [1×P1 to 2.2×P1]:1.

[0024] Thus, the present invention relates to a particulate material wherein the porous carbon framework comprises both micropores and mesopores, the minimum total volume of the micropores and mesopores being at least 0.6 cm 3 / g. The total volume of micropores and mesopores is expressed in this paper as P1cm 3 P1 itself is a dimensionless quantity having a value of at least 0.6, which is also used to relate the available pore volume to the weight ratio of silicon in the particulate material.

[0025] According to conventional IUPAC terminology, the term "microporous" is used herein to refer to pores with a diameter less than 2 nm, the term "mesoporous" is used herein to refer to pores with a diameter of 2-50 nm, and the term "macroporous" is used herein to refer to pores with a diameter greater than 50 nm.

[0026] The pore volume is distributed between micropores and mesopores, such that the volume fraction of micropores is in the range of 0.1 to 0.9 based on the total volume of micropores and mesopores. The volume fraction of micropores (based on the total volume of micropores and mesopores) is represented herein by the symbol , and the volume fraction of mesopores (based on the total volume of micropores and mesopores) is represented by the symbol So it will be understood

[0027] The porous carbon framework is also defined by a pore volume that is generally biased toward smaller pores, such that at least 75% of the total micropore and mesopore volume is in the form of pores having a diameter of no greater than 20 nm. The volume fraction of pores having a diameter of no greater than 20 nm (based on the total volume of micropores and mesopores) is represented herein by the symbol Indicates that the symbol and The corresponding volume fractions are used to define pores with diameters not exceeding 10 nm and not exceeding 5 nm, respectively.

[0028] In addition, the porous carbon framework is characterized by a D 50 Granularity limitation.

[0029] For the avoidance of doubt, P1 as used herein relates to the pore volume of the porous carbon skeleton when measured alone, i.e., the pore volume of the porous carbon skeleton in the absence of silicon or any other material occupying the pores of the porous carbon skeleton. Similarly, the volume of micropores, mesopores and macropores in the porous carbon skeleton mentioned herein and any distribution of pore volume within the porous carbon skeleton refer to the internal pore volume of the porous carbon skeleton alone (i.e., in the absence of any silicon or other material occupying the pore volume).

[0030] The weight ratio of silicon to the porous carbon framework in the composite particles is in the range of [1×P1 to 2.2×P1]: 1. Therefore, the weight ratio of silicon to the porous carbon framework is proportional to the available pore volume in the porous carbon framework, so that considering that the silicon density is about 2.3 g / cm 3 , a weight ratio of [1×P1]:1 corresponds to about 43% v / v of the pores of the porous carbon framework being occupied by silicon. The upper limit of the ratio of [2.2×P1]:1 corresponds to about 95% v / v of the pores of the porous carbon framework being occupied by silicon. Typically, these ratios are calculated based on pure carbon and pure silicon.

[0031] Elemental silicon is located in the micropores and / or mesopores in the form of multiple nano-sized silicon domains. As used herein, the term "nano-sized silicon domain" refers to nano-sized silicon bodies located within the pores of the porous carbon framework. The maximum size of the nano-sized silicon domain is limited by the pore size of the pore in which the silicon is located.

[0032] Thus, the present invention is generally directed to a particulate material in which nanosized silicon domains occupy a majority of the pore volume of a porous carbon framework, wherein the pore volume is distributed between small mesopores (up to 20 nm in diameter) and micropores. It has been found that this particle configuration provides electroactive materials having very high gravimetric and volumetric capacities after lithiation, and high reversible capacity retention over multiple charge-discharge cycles.

[0033] Without being bound by theory, it is believed that locating the nano-sized silicon domains within small mesopores and / or micropores first provides a fine silicon structure that can be lithiated and delithiated without excessive structural stress. It is believed that these very fine silicon domains have lower resistance to elastic deformation and higher fracture resistance than larger silicon structures. By ensuring that a higher proportion of the pore volume is occupied by silicon, the granular material of the present invention has a high capacity. In addition, as described above, by locating the nano-sized silicon domains within small mesopores and / or micropores, only a small area of ​​the silicon surface is accessible to the electrolyte, thereby limiting SEI formation.

[0034] The inventors have discovered that achieving the dual goals of high capacity and high reversible capacity retention depends on careful control of the pore size distribution. Although very fine silicon structures within the micropores can be expected to be most efficiently reversibly lithiated, it has been found that porous carbon frameworks with an excess of microporous fractions can accommodate less than the optimal amount of silicon, resulting in a lower volumetric capacity of the material. Without being bound by theory, it is believed that deposition of silicon into very highly microporous carbon frameworks results in the formation of silicon structures (such as caps or walls) that block access to the unoccupied pore volume, thereby limiting the achievable silicon loading.

[0035] However, if silicon is deposited into a carbon framework with very high mesoporosity, the silicon nanostructure is unsuitably large and the carbon wall thickness increases. As a result, although higher volumetric capacity can be achieved, both the silicon nanostructure and the porous carbon framework are subjected to excessive structural strain during lithiation, especially when lithiation is to maximum capacity, and the same is true in a hybrid anode that also contains graphite as an electroactive material. This excessive structural strain may lead to the rupture of the silicon nanostructure and the porous carbon framework. Thus, the additional exposure of silicon to the electrolyte from the ruptured surface in subsequent charge-discharge cycles means that SEI formation may become a significant damage mechanism leading to capacity loss. By controlling the relative volume fractions of micropores and mesopores and by ensuring that the mesopore volume is largely limited to pores below 20nm, the granular material of the present invention avoids these damage mechanisms and maintains a high reversible capacity over multiple charge-discharge cycles while also accommodating a large relative proportion of silicon in the pore volume of the porous carbon framework. This is in sharp contrast to the excessive and unconstrained SEI formation that is a feature of materials disclosed by, for example, Guo (see above).

[0036] Although lithiation of silicon may result in some external expansion of the entire composite, careful control of the micropore and mesopore volume fractions and the size distribution of the mesopore volume fraction toward smaller pore sizes ensures that the particle material can reversibly deform without fracturing over multiple charge-discharge cycles. Thus, the stresses on the carbon framework and silicon material are controlled to acceptable levels without significant capacity loss over a large number of charge-discharge cycles.

[0037] Due to the unique particle structure of the composite material of the present invention, the silicon in the granular material of the present invention has electrochemical performance comparable to that of fine silicon nanoparticles, without causing the disadvantages of excessive SEI formation and poor dispersibility, which make discrete silicon nanoparticles unsuitable for commercial use as electrode materials. The higher volume content of silicon in the granular material makes it particularly suitable for use as a component of a hybrid anode.

[0038] The porous carbon framework suitably comprises a three-dimensional interconnected open pore network comprising a combination of micropores and / or mesopores and optionally a small volume of macropores. The porous carbon framework is characterized by a high pore volume in the form of micropores and / or mesopores. The total volume of micropores and mesopores (i.e., the total pore volume in the range of 0 to 50 nm) is referred to herein as P1cm 3 / g, wherein P1 represents a dimensionless natural number having a value of at least 0.6. As described above, the value of P1 is also used to relate the available pore volume in the porous carbon framework to the weight ratio of silicon to the porous carbon framework as described above.

[0039] Preferably, the value of P1 is at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1. More preferably, the value of P1 is at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85. Optionally, the total volume of micropores and mesopores may be greater than 1 cm 3 / g, for example, P1 may be at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2.

[0040] The use of a high porosity carbon framework is advantageous because it enables a larger amount of silicon to be accommodated within the pore structure, and it has been found that a high porosity carbon framework in which the pore volume is primarily in the form of micropores and smaller mesopores has sufficient strength to accommodate the volume expansion of silicon without fracturing or otherwise degrading the porous carbon framework.

[0041] The internal pore volume of the porous carbon framework is limited to a value at which the increased brittleness of the porous carbon framework outweighs the advantages of the increased pore volume for accommodating a greater amount of silicon. Typically, the value of P1 may not exceed 2.2. However, preferably, the value of P1 may not exceed 2, or not exceed 1.8, or not exceed 1.6, or not exceed 1.5, or not exceed 1.4, or not exceed 1.3, or not exceed 1.2, or not exceed 1.1, or not exceed 1.0, or not exceed 0.9. More preferably, the value of P1 does not exceed 1.2, or does not exceed 1.1, or does not exceed 1.0, or does not exceed 0.9.

[0042] According to the present invention, the value of P1 may be, for example, in the range of 0.6 to 2 (i.e., the total volume of micropores and mesopores is 0.6 to 2 cm 3 / g). For example, P1 can be in the range of 0.6 to 1.8, or in the range of 0.65 to 1.8, or in the range of 0.7 to 1.8, or in the range of 0.75 to 1.8, or in the range of 0.8 to 1.8, or in the range of 0.85 to 1.8, or in the range of 0.9 to 1.8, or in the range of 0.65 to 1.7, or in the range of 0.7 to 1.7, or in the range of 0.75 to 1.7, or in the range of 0.8 to 1.7, or in the range of 0.85 to 1.7, or in the range of 0.9 to 1.7, or in the range of 0.95 to 1.7, or in the range of 0.7 to 1.6, or in the range of 0.75 to 1 .6, or in the range of 0.8 to 1.6, or in the range of 0.85 to 1.6, or in the range of 0.9 to 1.6, or in the range of 0.95 to 1.6, or in the range of 1 to 1.6, or in the range of 0.75 to 1.5, or in the range of 0.8 to 1.5, or in the range of 0.85 to 1.5, or in the range of 0.9 to 1.5, or in the range of 0.95 to 1.5, or in the range of 1 to 1.5, or in the range of 0.8 to 1.4, or in the range of 0.85 to 1.4, or in the range of 0.95 to 1.4, or in the range of 1 to 1.4.

[0043] Preferably, the value of P1 can be, for example, in the range of 0.6 to 1.4, or in the range of 0.65 to 1.4, or in the range of 0.7 to 1.4, or in the range of 0.75 to 1.4, or in the range of 0.6 to 1.3, or in the range of 0.65 to 1.3, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.6 to 1.2, or in the range of 0.65 to 1.2, or in the range of 0.7 to 1.2, or in the range of 0.6 to 1, or in the range of 0.65 to 1, or in the range of 0.7 to 1, or in the range of 0.75 to 1, or in the range of 0.6 to 0.9, or in the range of 0.65 to 0.9, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.

[0044] Volume fraction of micropores It is preferably in the range of 0.15 to 0.85, and more preferably in the range of 0.2 to 0.8.

[0045] Preferably, In the range of 0.45 to 0.85, more preferably in the range of 0.5 to 0.8, more preferably in the range of 0.5 to 0.75, and more preferably in the range of 0.5 to 0.7, in order to particularly utilize the high capacity retention rate of the very fine silicon nanostructure located in the micropores. For example, It may be in the range of 0.55 to 0.8, or in the range of 0.6 to 0.8, or in the range of 0.6 to 0.75.

[0046] Alternatively, It may be in the range of 0.2 to 0.5, more preferably in the range of 0.3 to 0.5, to particularly exploit opportunities of high silicon loading.

[0047] As discussed above, the pore volume is generally biased toward smaller pores, such that at least 75% of the total micropore and mesopore volume of the porous carbon framework is in the form of pores having a diameter of no more than 20 nm. More preferably, It is at least 0.8, more preferably at least 0.85, more preferably at least 0.9.

[0048] Preferably, based on the total volume of micropores and mesopores, is at least 0.70, or at least 0.75, or at least 0.8, or at least 0.85. More preferably, based on the total volume of micropores and mesopores, is at least 0.75, or at least 0.8, or at least 0.85. Thus, in preferred embodiments, at least 75% of the total microporous and mesoporous volume of the porous carbon framework is in the form of pores having a diameter of no more than 10 nm and more preferably no more than 5 nm.

[0049] A small portion of pores with diameters in the larger mesoporous range can advantageously facilitate access of the electrolyte to the silicon domains. Thus, pores with diameters in the range of 10 to 50 nm (i.e., larger mesopores) can optionally account for no more than 1%, or no more than 2%, or no more than 5%, or no more than 10% of the total micropore and mesopore volume of the porous carbon framework.

[0050] The volume ratio of micropores to mesopores in the porous carbon skeleton may be substantially in the range of 100:0 to 0: 100. Preferably, the volume ratio of micropores to mesopores is 90:10 to 55:45, or 90:10 to 60:40, or 85:15 to 65:35.

[0051] The pore size distribution of the porous carbon framework can be unimodal, bimodal or multimodal. As used herein, the term "pore size distribution" relates to the distribution of the pore size of the porous carbon framework relative to the cumulative total internal pore volume. Bimodal or multimodal pore size distributions may be preferred because the close proximity between the smallest pores and pores with larger diameters provides the advantage of efficient ion transport from the porous network to the silicon. Therefore, the particulate material has high ion diffusivity and therefore improved rate performance.

[0052] Suitably, the bimodal or multimodal pore size distribution comprises a peak pore size in the micropore range and a peak pore size in the mesopore size range, which differ from each other by a factor of 5 to 20, more preferably by a factor of about 10. For example, the porous carbon framework may have a bimodal pore size distribution comprising a peak at a pore size of 1.5 nm and a peak at a pore size of 15 nm.

[0053] According to the method described in ISO 15901-2 and ISO 15901-3, nitrogen adsorption was performed at 77K down to 10 -6 The relative pressure p / p0 of quenched solid density functional theory (QSDFT) is used to determine the total volume of micropores and mesopores and the pore size distribution of micropores and mesopores. Nitrogen adsorption is a technique for characterizing the porosity and pore size distribution of a material by condensing a gas in the pores of a solid. As the pressure increases, the gas first condenses in the pores with the smallest diameter, and the pressure increases until a saturation point is reached, at which all pores are filled with liquid. The nitrogen pressure is then gradually reduced to evaporate the liquid from the system. Analysis of the adsorption and desorption isotherms and the hysteresis between them enables the determination of pore volume and pore size distribution. Suitable instruments for measuring pore volume and pore size distribution by nitrogen adsorption include TriStar II and TriStar IIPlus porosity analyzers (which can be obtained by Micromeritics Instrument Corporation in the United States), and Autosorb IQ porosity analyzers (which can be obtained by Quantachrome Instruments).

[0054] Nitrogen adsorption is effective for measuring the pore volume and pore size distribution of pores with a diameter of up to 50 nm, but is less reliable for pores with much larger diameters. For the purposes of the present invention, therefore, only pores with a diameter of up to 50 nm (including 50 nm) are used to determine the pore volume and pore size distribution. As described above, the value of P1 is determined by considering only pores with a diameter of up to 50 nm (including 50 nm) (i.e., only micropores and mesopores), and is also determined relative to the total volume of only micropores and mesopores. and The value of .

[0055] Given the limitations of available analytical techniques, it is not possible to measure the pore volume and pore size distribution over the entire range of micropores, mesopores, and macropores using a single technique. In the case where the porous carbon framework includes macropores, the volume of pores in the range of greater than 50 nm to a maximum of 100 nm is considered herein to have a P2 cm 3 / g and is measured by mercury intrusion porosimetry. As described above, the value of P2 relates to the pore volume of the porous carbon framework when measured alone, ie, in the absence of silicon or any other material occupying the pores of the porous carbon framework.

[0056] For the avoidance of doubt, the value of P2 takes into account only pores with diameters from greater than 50 nm up to and including 100 nm, i.e. it includes only the volume of macropores with diameters up to 100 nm. For the determination of the value of P2, any pore volume measured by mercury intrusion at pore sizes below 50 nm is not taken into account (as described above, nitrogen adsorption is used to characterize mesopores and micropores). For the purposes of the present invention, the pore volume measured by mercury intrusion at a size above 100 nm is assumed to be the interparticle porosity and is also not taken into account when determining the value of P2.

[0057] Mercury intrusion porosimetry is a technique for characterizing the porosity and pore size distribution of a material by applying varying levels of pressure to a sample of the material immersed in mercury. The pressure required to cause mercury to penetrate into the pores of the sample is inversely proportional to the size of the pores. The values ​​obtained by mercury intrusion porosimetry reported herein are obtained according to ASTM UOP578-11, where for mercury at room temperature, the surface tension γ is 480 mN / m and the contact angle is is 140°. The density of mercury at room temperature is 13.5462 g / cm 3 A variety of high precision mercury porosimetry instruments are commercially available, such as the AutoPore IV series of automated mercury porosimeters, available from Micromeritics Instrument Corporation in the United States. For a complete overview of mercury porosimetry, reference may be made to PA Webb and C. Orr, "Analytical Methods in Fine Particle Technology", 1997, Micromeritics Instrument Corporation, ISBN 0-9656783-0.

[0058] The volume of macropores (and therefore the value of P2) is preferably small compared to the volume of micropores and mesopores (and therefore the value of P1). Although a small portion of macropores may be useful to facilitate the entry of electrolyte into the pore network, the advantages of the present invention are substantially obtained by accommodating silicon in micropores and smaller mesopores.

[0059] Therefore, according to the present invention, the total volume of the macropores in the porous carbon framework measured by mercury intrusion porosimetry is P2 cm 3 / g, wherein the value of P2 is preferably not more than 0.2×P1, or not more than 0.1×P1, or not more than 0.05×P1, or not more than 0.02×P1, or not more than 0.01×P1, or not more than 0.005×P1.

[0060] In preferred embodiments, the value of P2 is no more than 0.3, or no more than 0.25, or no more than 0.20, or no more than 0.15, or no more than 0.1, or no more than 0.05. As discussed above with respect to larger mesopores, a small pore volume fraction in the macropore range can advantageously promote electrolyte access to silicon.

[0061] The open pore network optionally comprises a hierarchical pore structure, ie, a pore structure in which there is a degree of pore size ordering, with smaller pores branching from larger pores.

[0062] It should be understood that intrusion techniques such as gas adsorption and mercury intrusion are only valid for determining the pore volume of pores accessible to nitrogen or mercury from outside the porous carbon framework. The porosity values ​​(P1 and P2) as specified herein should be understood to refer to the volume of open pores (pores accessible to the fluid from outside the porous carbon framework). In this article, when specifying porosity values, completely enclosed pores that cannot be identified by nitrogen adsorption or mercury intrusion should not be considered. Similarly, for determining the value of P1, any pore volume located in pores that are small enough to be below the detection limit of nitrogen adsorption is also not considered.

[0063] The porous carbon framework may comprise crystalline carbon or amorphous carbon, or a mixture of amorphous carbon and crystalline carbon.The porous carbon framework may be a hard carbon or a soft carbon framework, and may be suitably obtained by known procedures involving pyrolysis of polymers or organic matter.

[0064] The BET surface area of ​​the porous carbon framework is preferably at least 750 m 2 / g, or at least 1,000m 2 / g, or at least 1,250m 2 / g, or at least 1,500m 2 / g. As used herein, the term "BET surface area" should be considered to mean the surface area per unit mass calculated from the measurement results of the physical adsorption of gas molecules on the solid surface using the Brunauer-Emmett-Teller principle according to ISO 9277. Preferably, the BET surface area of ​​the conductive porous particle skeleton does not exceed 4,000 m 2 / g, or not more than 3,500m 2 / g, or not more than 3,250m 2 / g, or not more than 3,000m 2 / g.

[0065] As used herein, the term "hard carbon" refers to carbon atoms found predominantly as sp in nanoscale polyaromatic domains. 2 The polyaromatic domains are cross-linked using chemical bonds such as C-O-C bonds. Due to the chemical cross-linking between the polyaromatic domains, hard carbon cannot be converted into graphite at high temperatures. Hard carbon has graphite-like properties, which is reflected by the large G band (~1600 cm-1) in the Raman spectrum. -1 However, the carbon is not completely graphitic, as evidenced by the distinct D band (~1350 cm -1 ) proved by.

[0066] As used herein, the term "soft carbon" also refers to polyaromatic domains in which carbon atoms are found predominantly in sp 2 The polyaromatic domains in soft carbon are associated by intermolecular forces rather than crosslinked by chemical bonds, as in hard carbon. This means that they will graphitize at high temperatures. The porous carbon framework preferably contains at least 50% sp 2 Hybridized carbon (measured by XPS). For example, the porous carbon framework may suitably contain 50% to 98% sp 2 Hybridized carbon, 55% to 95% sp 2 Hybridized carbon, 60% to 90% sp 2 Hybridized carbon, or 70% to 85% sp 2 Hybridized carbon.

[0067] A wide variety of different materials can be used to prepare suitable porous carbon skeletons. Examples of organic materials that can be used include: plant biomass, which includes lignocellulosic materials (such as coconut shells, rice husks, wood, etc.), and fossil carbon sources, such as coal. Examples of polymer materials that form porous carbon skeletons during pyrolysis include: phenolic resins, novolac resins, asphalt, melamine, polyacrylates, polystyrene, polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), and various copolymers containing monomer units of acrylates, styrene, α-olefins, vinyl pyrrolidone and other ethylenically unsaturated monomers. Depending on the raw materials and conditions of the pyrolysis process, a variety of hard carbon materials are available in the art.

[0068] The porous carbon framework may be subjected to a chemical or gas activation process to increase the volume of the mesopores and micropores. Suitable activation processes include contacting the pyrolytic carbon with one or more of oxygen, water vapor, CO, CO2, and KOH at a temperature in the range of 600 to 1000°C.

[0069] Mesopores can also be obtained by known templating processes using removable pore formers such as MgO and other colloidal or polymer templates that can be removed by thermal or chemical means after pyrolysis or activation.

[0070] Porous carbon framework 50 The particle size may be in the range of 0.5 to 20 μm. 50 The particle size is at least 1 μm, more preferably at least 2 μm, for example at least 3 μm, or at least 4 μm, or at least 5 μm. Preferably, the D of the particulate material is 50 The particle size is no more than 18 μm, more preferably no more than 16 μm, more preferably no more than 14 μm, more preferably no more than 12 μm, more preferably no more than 10 μm, for example no more than 9 μm, or no more than 8 μm. More preferably, D 50 The particle size is preferably not more than 10 μm, or not more than 9 μm, or not more than 8 μm, or not more than 7 μm, or not more than 6 μm, or not more than 5 μm.

[0071] For example, the D 50 The particle size may be in the range of 1 to 12 μm, or in the range of 1 to 10 μm, or in the range of 2 to 10 μm, or in the range of 2 to 8 μm, or in the range of 2 to 6 μm, or in the range of 3 to 10 μm, or in the range of 3 to 8 μm, or in the range of 3 to 7 μm, or in the range of 3 to 6 μm, or in the range of 3 to 5 μm.

[0072] The amount of silicon in the porous carbon framework is related to the available pore volume by requiring the weight ratio of silicon in the composite particles to the porous carbon framework to be in the range of [1×P1 to 2.2×P1]: 1. This relationship takes into account the density of silicon and the pore volume of the porous carbon framework to define the weight ratio of silicon at which the internal pore volume (P1 cm) of the porous carbon framework is 3 / g) is occupied by silicon at approximately 43% to 95% v / v (in the uncharged state).

[0073] Preferably, the weight ratio of silicon to the porous carbon skeleton is at least 1.1×P1, more preferably at least 1.15×P1, more preferably at least 1.2×P1, more preferably at least 1.25×P1, more preferably at least 1.3×P1, more preferably at least 1.35×P1, more preferably at least 1.4×P1.

[0074] In the case where the porous carbon framework comprises a relatively high ratio of mesopores to micropores (e.g. In the range of 0.2 to 0.5 or in the range of 0.3 to 0.5), the weight ratio of silicon to the porous carbon skeleton can be still higher, for example at least 1.45×P1, more preferably at least 1.5×P1, more preferably at least 1.55×P1, more preferably at least 1.6×P1, more preferably at least 1.65×P1, more preferably at least 1.7×P1.

[0075] By requiring the weight ratio of silicon to the porous carbon skeleton in the composite particles to be at least 1×P1, the minimum weight ratio of silicon to the porous carbon skeleton is made equal to the mesoporous fraction. More preferably, the weight ratio of silicon to the porous carbon framework is at least The value given by The value given by The value given by The value given by The value given is (provided that the value is at least 1×P1). With higher values, the minimum amount of silicon in the composite particles is also higher. This relationship between the mesopore fraction and the minimum weight ratio of silicon to the porous carbon framework ensures that the porous carbon framework with a higher mesopore fraction is occupied to a greater extent by silicon, thereby optimizing the volume capacity of the particulate material. Ensuring that the porous carbon framework with a higher mesopore fraction has a higher minimum silicon loading also reduces the likelihood that larger micropores will be partially occupied by silicon, thereby reducing the silicon surface area exposed to the electrolyte, thereby limiting undesirable SEI formation.

[0076] The maximum weight ratio of silicon to the porous carbon framework is also related to the mesoporous fraction by requiring that the weight ratio of silicon to the porous carbon framework in the composite particles does not exceed the value given by 1.9×P1. More preferably, the weight ratio of silicon to the porous carbon framework is no more than The value given by The value given (provided that the value does not exceed 1.9×P1). The relationship between the mesoporous fraction and the maximum weight ratio of the porous carbon skeleton ensures that the porous carbon skeleton with a higher micropore fraction is not excessively filled with silicon. As described above, in the case where the porous carbon skeleton is more microporous due to the possibility of forming a wall or cover that encapsulates the occupied pore volume, it may be more difficult to achieve a very high ratio of silicon. In addition, in the case where the porous carbon skeleton is more microporous, the diffusion of lithium through the very fine silicon structure becomes rate-limited, which reduces the rate capacity of the particulate material. Therefore, controlling the upper limit of the silicon ratio ensures the extent to which the electrolyte enters the internal pore volume of the porous carbon skeleton, which promotes the transport of lithium ions to the silicon domain.

[0077] Preferably, the mass of silicon in the composite particles is substantially or completely located within the pores of the porous carbon framework in the form of the above-mentioned nano-sized silicon domains. For example, it is preferred that at least 90% by weight, more preferably at least 95% by weight, more preferably at least 98% by weight, more preferably at least 99% by weight of the mass of silicon in the composite particles is located within the internal pore volume of the porous carbon framework, so that no or very little silicon is located on the outer surface of the composite particles.

[0078] The particulate materials of the present invention may be further characterized by their thermogravimetric analysis (TGA) properties in air. Preferably, the particulate material contains no more than 10% unoxidized silicon at 800°C, as measured by TGA in air at a heating rate of 10°C / min. More preferably, the particulate material contains no more than 5% or no more than 2% unoxidized silicon at 800°C, as measured by TGA in air at a heating rate of 10°C / min.

[0079] The amount of unoxidized silicon was determined from characteristic TGA traces of these materials. The mass increase at about 300-500° C. corresponds to the initial oxidation of silicon to SiO2, followed by a mass loss at about 500-600° C. as carbon is oxidized to CO2 gas. Above about 600° C., there is a further mass increase corresponding to the continued conversion of silicon to SiO2, increasing to an asymptotic value above 1000° C. as silicon oxidation is completed.

[0080] For the purposes of this analysis, it is assumed that any mass increase above 800°C corresponds to oxidation of silicon to SiO2, and that the total mass at the completion of oxidation is SiO2. This enables the percentage of silicon that is not oxidized at 800°C to be determined (as a proportion of the total amount of silicon) according to the following formula:

[0081] Z=1.875×[(M f -M800 ) / M f ]×100%

[0082] Where Z is the percentage of silicon that is not oxidized at 800°C, M f is the mass of the sample at the completion of oxidation, and M 800 is the mass of the sample at 800 °C.

[0083] Without being bound by theory, it is understood that the temperature at which silicon is oxidized under TGA corresponds roughly to the length scale of the oxide coating on silicon, because oxygen atoms diffuse through the oxide layer and are thermally activated. The size of the silicon nanostructures and their location limit the length scale of the oxide coating thickness. Therefore, it is understood that silicon deposited in micropores and mesopores will oxidize at lower temperatures than silicon deposits on particle surfaces because there is a necessarily thinner oxide coating on these structures. Therefore, the preferred materials according to the present invention exhibit essentially complete oxidation of silicon at low temperatures, which is consistent with the small length scale of the silicon nanostructures located in the micropores and smaller mesopores. For the purposes of the present invention, the oxidation of silicon at 800°C is assumed to be silicon on the outer surface of the porous carbon skeleton. This is also referred to as "rough silicon" in this article.

[0084] The silicon is preferably amorphous silicon. Amorphous silicon is believed to have better properties as an electrically active material. The morphology of the silicon can be determined using X-ray diffraction (XRD) by known procedures.

[0085] Preferably, the volume of micropores and mesopores in the composite particles (ie in the presence of silicon) measured by nitrogen adsorption does not exceed 0.15x P1, or does not exceed 0.10x P1, or does not exceed 0.05x P1, or does not exceed 0.02x P1.

[0086] The weight ratio of silicon to the porous carbon skeleton can be determined by elemental analysis. Elemental analysis is used to determine the weight percentage of both silicon and carbon in the composite particles. Optionally, the amount of hydrogen, nitrogen and oxygen can also be determined by elemental analysis. Preferably, elemental analysis is also used to determine the weight percentage of carbon (and optional hydrogen, nitrogen and oxygen) in a separate porous carbon skeleton. Determining the weight percentage of carbon in a separate porous carbon skeleton takes into account the possibility that the porous carbon skeleton contains a small amount of heteroatoms within its molecular skeleton. The two measurements performed together make it possible to reliably determine the weight percentage of silicon relative to the entire porous carbon skeleton.

[0087] The silicon content is preferably determined by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy). A variety of ICP-OES instruments are commercially available, such as The carbon content (and, if desired, the hydrogen content, nitrogen content and oxygen content) of the composite particles and the individual porous carbon frameworks is preferably determined by IR absorption. A suitable instrument for determining the carbon content, hydrogen content, nitrogen content and oxygen content is Micro Elemental Analyzer (available from Leco Corporation).

[0088] The composite particles preferably have a low total oxygen content. Oxygen may be present in the composite particles, for example, as part of the porous carbon framework or as an oxide layer on any exposed silicon surface. Preferably, the total oxygen content of the composite particles is less than 15 wt%, more preferably less than 10 wt%, more preferably less than 5 wt%, for example less than 2 wt%, or less than 1 wt%, or less than 0.5 wt%.

[0089] Silicon may optionally contain a small amount of one or more dopants. Suitable dopants include boron and phosphorus, other n-type or p-type dopants, nitrogen or germanium. Preferably, the dopant is present in a total amount of no more than 2 wt % based on the total amount of silicon and the one or more dopants.

[0090] For the avoidance of doubt, the term "particle size" as used herein refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, wherein the particle volume is understood to include the volume of any intra-particle pores. 50 ” and “D 50 "Particle size" refers to the median particle size based on volume, that is, the diameter at which 50% of the volume of the particle population is below a certain diameter. As used herein, the term "D 10 ” and “D 10 The term "particle size" as used herein refers to the 10th percentile volume-based median particle size, i.e., the diameter below which 10% of the volume of the particle population is measured. 90 ” and “D 90 "Particle size" refers to the 90th percentile volume-based median particle size, i.e., the diameter below which 90% of the volume of the particle population is measured.

[0091] Particle size and particle size distribution can be determined by conventional laser diffraction techniques according to ISO 13320:2009. Laser diffraction relies on the principle that particles will scatter light at an angle that varies depending on the size of the particle, and that multiple particles will produce a scattered light pattern defined by intensity and angle that can be related to the particle size distribution. A variety of laser diffraction instruments are commercially available for rapid and reliable determination of particle size distribution. Unless otherwise stated, particle size distribution measurements indicated or reported herein were made by conventional Malvern Mastersizer from Malvern Instruments. TM Measured by Malvern Mastersizer 3000 particle size analyzer. TM The 3000 particle size analyzer operates by projecting a helium-neon gas laser beam through a transparent pool containing particles of interest suspended in an aqueous solution. The light that hits the particles is scattered by angles inversely proportional to the particle size, and a photodetector array measures the intensity of the light at multiple predetermined angles, and the intensity measured at different angles is processed by a computer using standard theoretical principles to determine the particle size distribution. The laser diffraction values ​​reported herein are obtained using a wet dispersion of particles in distilled water. The particle refractive index is 3.50, and the dispersant index is 1.330. The particle size distribution is calculated using the Mie scattering model.

[0092] D of composite particles 50 The particle size may be in the range of 0.5 to 20 μm. 50 The particle size is at least 1 μm, more preferably at least 2 μm, for example at least 3 μm, or at least 4 μm, or at least 5 μm. Preferably, the D of the particulate material is 50 The particle size is no more than 18 μm, more preferably no more than 16 μm, more preferably no more than 14 μm, more preferably no more than 12 μm, more preferably no more than 10 μm, for example no more than 9 μm, or no more than 8 μm.

[0093] For example, the D of a composite particle 50 The particle size may be in the range of 1 to 12 μm, or 1 to 10 μm, or 2 to 10 μm, or 3 to 10 μm, or 3 to 8 μm. Particles within these size ranges and having the porosity and pore size distribution described herein are ideally suited for use in hybrid anodes for metal ion batteries due to their dispersibility in slurries, their structural robustness, their capacity retention with repeated charge-discharge cycles, and their ability to occupy the void space between conventional graphite particles used in electrodes for metal ion batteries.

[0094] D of composite particles 10The particle size is preferably at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10 The particle size is maintained above 0.2 μm, reducing the possibility of undesirable agglomeration of submicron sized particles, resulting in improved dispersion of the particulate material and improved capacity retention.

[0095] D of composite particles 90 The particle size is preferably no more than 40 μm, or no more than 30 μm, or no more than 20 μm, or no more than 15 μm, or no more than 12 μm, or no more than 10 μm. The presence of very large particles leads to uneven filling of particles in the electrode active layer, thereby destroying the formation of a dense electrode layer, especially an electrode layer with a thickness in the conventional range of 20 to 50 μm. Therefore, it is preferred that D 90 The particle size does not exceed 20 μm, and more preferably is even smaller.

[0096] The composite particles preferably have a narrow size distribution span. For example, the particle size distribution span (defined as (D 90 -D 10 ) / D 50 ) is preferably 5 or less, more preferably 4 or less, more preferably 3 or less, more preferably 2 or less, and most preferably 1.5 or less. By maintaining a narrow size distribution span, efficient filling of particles into a dense electrode layer can be more easily achieved.

[0097] The shape of the composite particles can be spherical. Spherical particles as defined herein can include both spherical particles and ellipsoidal particles, and the shape of the composite particles of the present invention can be suitably defined with reference to the sphericity and aspect ratio of the particles of the present invention. It is found that spherical particles are particularly well suited for dispersions in slurries without forming agglomerates. In addition, it is unexpectedly found that the use of porous spherical particles provides a further improvement in strength when compared to porous particles and porous particle fragments of irregular morphology.

[0098] The sphericity of an object is conventionally defined as the ratio of the surface area of ​​a sphere to the surface area of ​​an object, wherein the object and the sphere have the same volume. However, it is actually difficult to measure the surface area and volume of individual particles at micrometer scale. However, highly accurate two-dimensional projections of micrometer-scale particles can be obtained by scanning electron microscopy (SEM) and by dynamic image analysis, wherein a digital camera is used to record the shadows projected by the particles. The term "sphericity" as used herein should be understood as the ratio of the area of ​​a particle projection to the area of ​​a circle, wherein the particle projection and the circle have the same perimeter. Therefore, for individual particles, the sphericity S can be defined as:

[0099]

[0100] Among them A m is the measured area of ​​the particle projection, and C m is the measured circumference of the particle projection. As used herein, the average sphericity S of a plurality of particles av is defined as:

[0101]

[0102] Where n represents the number of particles in the population.

[0103] As used herein, the term "quasi-spherical" applied to the composite particles of the present invention should be understood to refer to materials having an average sphericity of at least 0.70. Preferably, the average sphericity of the porous quasi-spherical particles of the present invention is at least 0.85, more preferably at least 0.90, more preferably at least 0.92, more preferably at least 0.93, preferably at least 0.94, more preferably at least 0.95. Optionally, the average sphericity of the porous quasi-spherical particles can be at least 0.96, or at least 0.97, or at least 0.98, or at least 0.99.

[0104] It is to be understood that in the case of any particles that are not perfectly spherical, the perimeter and area of ​​the two-dimensional particle projection will depend on the orientation of the particle. However, the effect of particle orientation can be offset by reporting the sphericity and aspect ratio as average values ​​obtained for multiple particles with random orientation. A variety of SEM and dynamic image analysis instruments are commercially available, making it possible to quickly and reliably determine the sphericity and aspect ratio of particulate materials. Unless otherwise stated, the sphericity values ​​as specified or reported herein are measured by the CamSizer XT particle analyzer from Retsch Technology GmbH. The CamSizer XT is a dynamic image analysis instrument that can obtain highly accurate distributions of the size and shape of particulate materials with sample volumes of 100 mg to 100 g, making it possible to calculate properties such as average sphericity and aspect ratio directly through the instrument.

[0105] The BET surface area of ​​the composite particles is preferably not more than 150 m 2 / g, or not more than 100m 2 / g, or not more than 80m 2 / g, or not more than 60m 2 / g, or not more than 40m 2 / g, or not more than 30m 2 / g, or not more than 25m 2 / g, or not more than 20m 2 / g, or not more than 15m 2 / g, or not more than 10m 2 / g. Generally, a low BET surface area is preferred to minimize the formation of a solid electrolyte interface (SEI) layer at the surface of the composite particles during the first charge-discharge cycle of an anode comprising the particulate material of the present invention. However, too low a BET surface area results in unacceptably low charge rates and capacities due to the inaccessibility of the bulk of the electroactive material to the metal ions in the surrounding electrolyte. For example, the BET surface area is preferably at least 0.1 m 2 / g, or at least 1m 2 / g, or at least 2m 2 / g, or at least 5m 2 / g. For example, the BET surface area can be 2 / g to 25m 2 / g, more preferably in the range of 2 to 15 m 2 / g range.

[0106] The particle material of the present invention has a specific charge capacity of 1200 to 2340 mAh / g upon first lithiation. Preferably, the particle material of the present invention has a specific charge capacity of at least 1400 mAh / g upon first lithiation.

[0107] The composite particles of the present invention are suitably prepared by chemical vapor infiltration (CVI) of a silicon-containing precursor into the pore structure of a porous carbon framework. As used herein, CVI refers to a process in which a gaseous silicon-containing gas is thermally decomposed on a surface to form elemental silicon and gaseous byproducts at the surface.

[0108] Suitable gaseous silicon-containing precursors include silane (SiH4), silane derivatives (e.g., disilane, trisilane and tetrasilane) and trichlorosilane (SiHCl3). The silicon-containing precursor can be used in pure form, or more generally as a mixture diluted with an inert carrier gas such as nitrogen or argon. For example, the silicon-containing precursor can be used in an amount in the range of 0.5-20 volume %, or 1-10 volume % or 1-5 volume % based on the total volume of the silicon-containing precursor and the inert carrier. The CVI process is suitably carried out with a low silicon precursor partial pressure at a total pressure of 101.3 kPa (i.e., 1 atm), and the remaining partial pressure is supplemented to atmospheric pressure using an inert filler gas such as hydrogen, nitrogen or argon. A deposition temperature in the range of 400-700°C is used, for example, 400-550°C, or 400-500°C, or 400-450°C or 450-500°C. The CVI process may suitably be carried out in a fixed bed reactor, a fluidised bed reactor (including a spouted bed reactor) or a rotary kiln.

[0109] A particular advantage of the present invention is that the porous carbon framework has a very high ratio of internal surface area to external surface area due to the very low pore size. As a result, deposition of silicon onto the internal surface of the porous carbon framework is kinetically favored. Thus, a very high proportion of the silicon in the composite particles of the present invention is in the form of nano-sized elemental silicon domains located within the micropores and / or mesopores of the porous carbon framework (e.g., as described above, at least 90% by weight of the mass of silicon in the composite particles, more preferably at least 95% by weight, more preferably at least 98% by weight, more preferably at least 99% by weight).

[0110] In contrast, the formation of silicon deposits on the outer surface of the porous carbon framework proceeds at a significantly lower rate, such that the composite particles typically contain very small amounts of external silicon on the outer surface of the porous carbon framework. Without being bound by theory, it is believed that the larger size of the silicon on the outer surface of the porous carbon framework means that the external silicon (referred to herein as "coarse silicon") is less able to cycle reversibly and results in proportionally larger amounts of silicon oxide and SEI formation, such that composite particles with large amounts of external silicon will have poor capacity retention after multiple charge and discharge cycles.

[0111] The granular material of the present invention may optionally include a conductive carbon coating. Suitably, the conductive carbon coating may be obtained by chemical vapor deposition (CVD). CVD is a method well known in the art and includes thermally decomposing a volatile carbon-containing gas (e.g., ethylene) onto the surface of the granular material. Alternatively, the carbon coating may be formed by depositing a solution of a carbon-containing compound onto the surface of the granular material and then thermally decomposing it. The conductive carbon coating has sufficient permeability to allow lithium to approach the interior of the composite particles without excessive resistance, thereby not reducing the rate performance of the composite particles. For example, the thickness of the carbon coating may suitably be in the range of 2 to 30 nm. Optionally, the carbon coating may be porous, and / or may only partially cover the surface of the composite particles.

[0112] The carbon coating has the following advantages: it further reduces the BET surface area of ​​the particle material by smoothing any surface defects and by filling any remaining surface micropores, thereby further reducing first cycle losses. In addition, the carbon coating increases the conductivity of the surface of the composite particles, thereby reducing the need for conductive additives in the electrode composition, and also creates an optimal surface for the formation of a stable SEI layer, resulting in improved capacity retention during cycling.

[0113] According to the first aspect of the present invention, there is also provided a granular material according to the following aspects 1-1 to 1-41. Aspect 1-1: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.7-1.4;

[0114] (ii) In the range of 0.5 to 0.8;

[0115] (iii) is at least 0.8;

[0116] (iv) D of porous carbon framework 50 The particle size is in the range of 1 to 18 μm. Aspect 1-2: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.7-1.4;

[0117] (ii) In the range of 0.5 to 0.8;

[0118] (iii) is at least 0.8;

[0119] (iv) D of porous carbon framework 50 The particle size is in the range of 1 to 12 μm. Aspects 1-3: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.7-1.4;

[0120] (ii) In the range of 0.5 to 0.8;

[0121] (iii) is at least 0.8;

[0122] (iv) D of porous carbon framework 50 The particle size is in the range of 2 to 8 μm. Aspects 1-4: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.7-1.4;

[0123] (ii) In the range of 0.5 to 0.8;

[0124] (iii) is at least 0.8;

[0125] (iv) D of porous carbon framework 50 The particle size is in the range of 2 to 8 μm. Aspects 1-5: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.7-1.4;

[0126] (ii) In the range of 0.5 to 0.8;

[0127] (iii) is at least 0.75;

[0128] (iv) D of porous carbon framework 50The particle size is in the range of 2 to 8 μm. Aspects 1-6: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.8-1.2;

[0129] (ii) In the range of 0.6 to 0.8;

[0130] (iii) is at least 0.8;

[0131] (iv) D of porous carbon framework 50 The particle size is in the range of 1 to 18 μm. Aspects 1-7: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.8-1.2;

[0132] (ii) In the range of 0.6 to 0.8;

[0133] (iii) is at least 0.8;

[0134] (iv) D of porous carbon framework 50 The particle size is in the range of 1 to 12 μm. Aspects 1-8: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.8-1.2;

[0135] (ii) In the range of 0.6 to 0.8;

[0136] (iii) is at least 0.8;

[0137] (iv) D of porous carbon framework 50 The particle size is in the range of 2 to 8 μm. Aspects 1-9: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.8-1.2;

[0138] (ii) In the range of 0.6 to 0.8;

[0139] (iii) is at least 0.8;

[0140] (iv) D of porous carbon framework 50 The particle size is in the range of 2 to 8 μm. Aspects 1-10: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.8-1.2;

[0141] (ii) In the range of 0.6 to 0.8;

[0142] (iii) is at least 0.75;

[0143] (iv) D of porous carbon framework 50 The particle size is in the range of 2 to 8 μm. Aspects 1-11: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.7-0.9;

[0144] (ii) In the range of 0.6 to 0.8;

[0145] (iii) is at least 0.75;

[0146] (iv) D of porous carbon framework 50 The particle size is in the range of 3 to 6 μm. Aspects 1-12: The granular material according to the first aspect of the present invention, wherein: (i) P1 is in the range of 0.7-1.4;

[0147] (ii) In the range of 0.5 to 0.8;

[0148] (iii) is at least 0.8;

[0149] (iv) D of porous carbon framework 50 Particle size ranges from 1 to 18 μm;

[0150] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0151] Aspects 1-13: The granular material according to the first aspect of the present invention, wherein:

[0152] (i) P1 is in the range of 0.7-1.4;

[0153] (ii) In the range of 0.5 to 0.8;

[0154] (iii) is at least 0.8;

[0155] (iv) D of porous carbon framework 50 Particle size ranges from 1 to 12 μm;

[0156] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0157] Aspects 1-14: The granular material according to the first aspect of the present invention, wherein:

[0158] (i) P1 is in the range of 0.7-1.4;

[0159] (ii) In the range of 0.5 to 0.8;

[0160] (iii) is at least 0.8;

[0161] (iv) D of porous carbon framework 50 Particle size ranges from 2 to 8 μm

[0162] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0163] Aspects 1-15: The granular material according to the first aspect of the present invention, wherein:

[0164] (i) P1 is in the range of 0.7-1.4;

[0165] (ii) In the range of 0.5 to 0.8;

[0166] (iii) is at least 0.8;

[0167] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0168] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0169] Aspects 1-16: The granular material according to the first aspect of the present invention, wherein:

[0170] (i) P1 is in the range of 0.7-1.4;

[0171] (ii) In the range of 0.5 to 0.8;

[0172] (iii) is at least 0.75;

[0173] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0174] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0175] Aspects 1-17: The granular material according to the first aspect of the present invention, wherein:

[0176] (i) P1 is in the range of 0.7-0.9;

[0177] (ii) In the range of 0.6 to 0.8;

[0178] (iii) is at least 0.75;

[0179] (iv) D of porous carbon framework 50 The particle size ranges from 3 to 6 μm;

[0180] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0181] Aspects 1-18: The granular material according to the first aspect of the present invention, wherein:

[0182] (i) P1 is in the range of 0.8-1.2;

[0183] (ii) In the range of 0.6 to 0.8;

[0184] (iii) is at least 0.8;

[0185] (iv) D of porous carbon framework 50 Particle size ranges from 1 to 18 μm;

[0186] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0187] Aspects 1-19: The granular material according to the first aspect of the present invention, wherein:

[0188] (i) P1 is in the range of 0.8-1.2;

[0189] (ii) In the range of 0.6 to 0.8;

[0190] (iii) is at least 0.8;

[0191] (iv) D of porous carbon framework50 Particle size ranges from 1 to 12 μm;

[0192] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0193] Aspects 1-20: The granular material according to the first aspect of the present invention, wherein:

[0194] (i) P1 is in the range of 0.8-1.2;

[0195] (ii) In the range of 0.6 to 0.8;

[0196] (iii) is at least 0.8;

[0197] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0198] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0199] Aspects 1-21: The granular material according to the first aspect of the present invention, wherein:

[0200] (i) P1 is in the range of 0.8-1.2;

[0201] (ii) In the range of 0.6 to 0.8;

[0202] (iii) is at least 0.8;

[0203] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0204] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0205] Aspects 1-22: The granular material according to the first aspect of the present invention, wherein:

[0206] (i) P1 is in the range of 0.8-1.2;

[0207] (ii) In the range of 0.6 to 0.8;

[0208] (iii) is at least 0.75;

[0209] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0210] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0211] Aspects 1-23: The granular material according to the first aspect of the present invention, wherein:

[0212] (i) P1 is in the range of 0.7-0.9;

[0213] (ii) In the range of 0.6 to 0.8;

[0214] (iii) is at least 0.75;

[0215] (iv) D of porous carbon framework 50 The particle size ranges from 3 to 6 μm;

[0216] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0217] Aspects 1-24: The granular material according to the first aspect of the present invention, wherein:

[0218] (i) P1 is in the range of 0.8-1.2;

[0219] (ii) In the range of 0.6 to 0.8;

[0220] (iii) is at least 0.8;

[0221] (iv) D of porous carbon framework 50 Particle size ranges from 1 to 18 μm;

[0222] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0223] Aspects 1-25: The granular material according to the first aspect of the present invention, wherein:

[0224] (i) P1 is in the range of 0.8-1.2;

[0225] (ii) In the range of 0.6 to 0.8;

[0226] (iii) is at least 0.8;

[0227] (iv) D of porous carbon framework 50 Particle size ranges from 1 to 12 μm;

[0228] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0229] Aspects 1-26: The granular material according to the first aspect of the present invention, wherein:

[0230] (i) P1 is in the range of 0.8-1.2;

[0231] (ii) In the range of 0.6 to 0.8;

[0232] (iii) is at least 0.8;

[0233] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0234] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0235] Aspects 1-27: The granular material according to the first aspect of the present invention, wherein:

[0236] (i) P1 is in the range of 0.8-1.2;

[0237] (ii) In the range of 0.6 to 0.8;

[0238] (iii) is at least 0.8;

[0239] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0240] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0241] Aspects 1-28: The granular material according to the first aspect of the present invention, wherein:

[0242] (i) P1 is in the range of 0.8-1.2;

[0243] (ii) In the range of 0.6 to 0.8;

[0244] (iii) is at least 0.75;

[0245] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0246] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0247] Aspects 1-29: The granular material according to the first aspect of the present invention, wherein:

[0248] (i) P1 is in the range of 0.7-0.9;

[0249] (ii) In the range of 0.6 to 0.8;

[0250] (iii) is at least 0.75;

[0251] (iv) D of porous carbon framework 50 The particle size ranges from 3 to 6 μm;

[0252] (v) The weight ratio of silicon to the porous carbon framework is at least The value given by The value given.

[0253] Aspects 1-30: The granular material according to the first aspect of the present invention, wherein:

[0254] (i) P1 is in the range of 0.7-1.4;

[0255] (ii) In the range of 0.5 to 0.8;

[0256] (iii) is at least 0.8;

[0257] (iv) D of porous carbon framework 50 Particle size ranges from 1 to 18 μm;

[0258] (v) The weight ratio of silicon to the porous carbon framework is in the range of [1.2×P1 to 1.8×P1]:1.

[0259] Aspect 1-31: The granular material according to the first aspect of the present invention, wherein:

[0260] (i) P1 is in the range of 0.7-1.4;

[0261] (ii) In the range of 0.5 to 0.8;

[0262] (iii) is at least 0.8;

[0263] (iv) D of porous carbon framework 50 Particle size ranges from 1 to 12 μm;

[0264] (v) The weight ratio of silicon to the porous carbon framework is in the range of [1.2×P1 to 1.8×P1]:1.

[0265] Aspect 1-32: The granular material according to the first aspect of the present invention, wherein:

[0266] (i) P1 is in the range of 0.7-1.4;

[0267] (ii) In the range of 0.5 to 0.8;

[0268] (iii) is at least 0.8;

[0269] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0270] (v) The weight ratio of silicon to the porous carbon framework is in the range of [1.2×P1 to 1.8×P1]:1.

[0271] Aspect 1-33: The granular material according to the first aspect of the present invention, wherein:

[0272] (i) P1 is in the range of 0.7-1.4;

[0273] (ii) In the range of 0.5 to 0.8;

[0274] (iii) is at least 0.8;

[0275] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0276] (v) The weight ratio of silicon to the porous carbon skeleton is in the range of [1.2×P1 to 1.8×P1]: 1. Aspect 1-34: The granular material according to the first aspect of the present invention, wherein:

[0277] (i) P1 is in the range of 0.7-1.4;

[0278] (ii) In the range of 0.5 to 0.8;

[0279] (iii) is at least 0.75;

[0280] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0281] (v) The weight ratio of silicon to the porous carbon skeleton is in the range of [1.2×P1 to 1.8×P1]: 1. Aspect 1-35: The granular material according to the first aspect of the present invention, wherein:

[0282] (i) P1 is in the range of 0.7-0.9;

[0283] (ii) In the range of 0.6 to 0.8;

[0284] (iii) is at least 0.75;

[0285] (iv) D of porous carbon framework 50 The particle size ranges from 3 to 6 μm;

[0286] (v) The weight ratio of silicon to the porous carbon skeleton is in the range of [1.2×P1 to 1.8×P1]: 1. Aspect 1-36: The granular material according to the first aspect of the present invention, wherein:

[0287] (i) P1 is in the range of 0.8-1.2;

[0288] (ii) In the range of 0.6 to 0.8;

[0289] (iii) is at least 0.8;

[0290] (iv) D of porous carbon framework 50 Particle size ranges from 1 to 18 μm;

[0291] (v) The weight ratio of silicon to the porous carbon skeleton is in the range of [1.2×P1 to 1.6×P1]: 1. Aspect 1-37: The granular material according to the first aspect of the present invention, wherein:

[0292] (i) P1 is in the range of 0.8-1.2;

[0293] (ii) In the range of 0.6 to 0.8;

[0294] (iii) is at least 0.8;

[0295] (iv) D of porous carbon framework 50 Particle size ranges from 1 to 12 μm;

[0296] (v) The weight ratio of silicon to the porous carbon skeleton is in the range of [1.2×P1 to 1.6×P1]: 1. Aspect 1-38: The granular material according to the first aspect of the present invention, wherein:

[0297] (i) P1 is in the range of 0.8-1.2;

[0298] (ii) In the range of 0.6 to 0.8;

[0299] (iii) is at least 0.8;

[0300] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0301] (v) The weight ratio of silicon to the porous carbon framework is in the range of [1.2×P1 to 1.6×P1]:1.

[0302] Aspects 1-39: The granular material according to the first aspect of the present invention, wherein:

[0303] (i) P1 is in the range of 0.8-1.2;

[0304] (ii) In the range of 0.6 to 0.8;

[0305] (iii) is at least 0.8;

[0306] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0307] (v) The weight ratio of silicon to the porous carbon framework is in the range of [1.2×P1 to 1.6×P1]:1.

[0308] Aspects 1-40: The granular material according to the first aspect of the present invention, wherein:

[0309] (i) P1 is in the range of 0.8-1.2;

[0310] (ii) In the range of 0.6 to 0.8;

[0311] (iii) is at least 0.75;

[0312] (iv) D of porous carbon framework 50 The particle size ranges from 2 to 8 μm;

[0313] (v) The weight ratio of silicon to the porous carbon framework is in the range of [1.2×P1 to 1.6×P1]:1.

[0314] Aspect 1-41: The granular material according to the first aspect of the present invention, wherein:

[0315] (i) P1 is in the range of 0.7-0.9;

[0316] (ii) In the range of 0.6 to 0.8;

[0317] (iii) is at least 0.75;

[0318] (iv) D of porous carbon framework 50 The particle size ranges from 3 to 6 μm;

[0319] (v) The weight ratio of silicon to the porous carbon framework is in the range of [1.2×P1 to 1.6×P1]:1.

[0320] According to the present invention, it should be understood that the preferred / optional features disclosed herein in relation to the first aspect of the present invention within the scope of the above-mentioned aspects 1-1 to 1-41 are also considered to be the preferred / optional features of aspects 1-1 to 1-41. Likewise, any features of the dependent claims within the scope of the above-mentioned aspects 1-1 to 1-41 should also be interpreted as if those claims also depend on aspects 1-1 to 1-41.

[0321] In the second aspect of the present invention, a composition comprising a particulate material according to the first aspect of the present invention and at least one other component is provided. Preferably, the composition according to the second aspect of the present invention can be used to form an active layer of an electrode. Such a composition may be referred to as an "electrode composition" herein. The particulate material used to prepare the composition of the second aspect of the present invention may have any of the features described as preferred or optional with respect to the first aspect of the present invention, and may be a particulate material according to any one of aspects 1-1 to 1-41.

[0322] Thus, there is provided a composition comprising a particulate material according to the first aspect of the invention and at least one further component selected from: (i) a binder; (ii) a conductive additive; and (iii) a further particulate electroactive material.

[0323] The composition is preferably a hybrid electrode composition comprising the particulate material according to the first aspect of the invention and at least one further particulate electroactive material.

[0324] The specific lithiation capacity of the at least one additional particulate electroactive material is preferably in the range of 100 to 600 mAh / g or 200 to 500 mAh / g. Examples of additional particulate electroactive materials include graphite, hard carbon, silicon, tin, germanium, gallium, aluminum and lead. The at least one additional particulate electroactive material is preferably selected from graphite and hard carbon, and most preferably, the at least one additional particulate electroactive material is graphite.

[0325] At least one additional particulate electroactive material D 50 The particle size is preferably in the range of 10 to 50 μm, preferably in the range of 10 to 40 μm, more preferably in the range of 10 to 30 μm, and most preferably in the range of 10 to 25 μm, for example in the range of 15 to 25 μm.

[0326] At least one additional particulate electroactive material D 10 The particle size is preferably at least 5 μm, more preferably at least 6 μm, more preferably at least 7 μm, more preferably at least 8 μm, more preferably at least 9 μm, and still more preferably at least 10 μm.

[0327] At least one additional particulate electroactive material D 90 The particle size is preferably not more than 100 μm, more preferably not more than 80 μm, more preferably not more than 60 μm, more preferably not more than 50 μm, and most preferably not more than 40 μm.

[0328] In a preferred embodiment, the at least one additional particulate electroactive material is selected from graphite and hard carbon particles having a D 50 The particle size is in the range of 10 to 50 μm. Still more preferably, the at least one additional particulate electroactive material is selected from graphite particles, wherein the D 50 The particle size ranges from 10 to 50 μm.

[0329] The at least one additional particulate electroactive material is preferably in the form of spheroidal particles having an average sphericity of at least 0.70, preferably at least 0.85, more preferably at least 0.90, more preferably at least 0.92, more preferably at least 0.93, more preferably at least 0.94, and most preferably at least 0.95.

[0330] The average aspect ratio of the at least one additional particulate electroactive material is preferably less than 3:1, preferably no more than 2.5:1, more preferably no more than 2:1, more preferably no more than 1.8:1, more preferably no more than 1.6:1, more preferably no more than 1.4:1, and most preferably no more than 1.2:1.

[0331] The particulate material of the present invention may comprise 0.5 to 80% by weight of the total dry weight of the electroactive material in the composition. For example, the particulate material of the present invention may comprise 2 to 70% by weight, or 4 to 60% by weight, or 5 to 50% by weight of the total dry weight of the electroactive material in the composition.

[0332] Where the composition is a hybrid electrode composition comprising at least one additional particulate electroactive material as described above, the electrode composition preferably comprises 1 to 20 wt%, or 2 to 15 wt%, or 2 to 10 wt%, or 2 to 5 wt% of the particulate material of the present invention, based on the total dry weight of the composition.

[0333] Furthermore, where the composition is a hybrid electrode composition, the electrode composition preferably comprises 10 to 98 wt%, or 15 to 97 wt%, or 20 to 97 wt%, or 25 to 97 wt% of at least one additional particulate electroactive material, based on the total dry weight of the composition.

[0334] The ratio of at least one further particulate electroactive material to the particulate material of the present invention is suitably in the range 50:50 to 99:1 by weight, more preferably in the range 60:40 to 98:2 by weight, more preferably in the range 70:30 to 97:3 by weight, more preferably in the range 80:20 to 96:4 by weight, and most preferably in the range 85:15 to 95:5 by weight.

[0335] The at least one additional particulate electroactive material and the particulate material of the present invention preferably together comprise at least 50wt%, more preferably at least 60wt%, more preferably at least 70wt%, and most preferably at least 80wt%, for example at least 85wt%, at least 90wt% or at least 95wt% of the total weight of the composition.

[0336] The composition may optionally include a binder. The binder serves to adhere the composition to the current collector and maintain the integrity of the composition. Examples of binders that can be used according to the present invention include polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, carboxymethyl cellulose (CMC), modified carboxymethyl cellulose (mCMC), sodium carboxymethyl cellulose (Na-CMC), polyvinyl alcohol (PVA), alginate and its alkali metal salts, styrene-butadiene rubber (SBR) and polyimide. The composition may include a mixture of multiple binders. Preferably, the binder includes a polymer selected from the following: polyacrylic acid (PAA) and its alkali metal salts, and modified polyacrylic acid (mPAA) and its alkali metal salts, SBR and CMC.

[0337] The binder may suitably be present in an amount of from 0.5 to 20 wt%, preferably from 1 to 15 wt% and most preferably from 2 to 10 wt% based on the total dry weight of the composition.

[0338] The binder may optionally be present in combination with one or more additives that modify the properties of the binder, such as crosslinking accelerators, coupling agents and / or adhesion promoters.

[0339] The composition may optionally include one or more conductive additives. Preferred conductive additives are non-electroactive materials that are included to improve the conductivity between the electroactive components of the electrode composition and the conductivity between the electroactive components of the electrode composition and the current collector. The conductive additive may be suitably selected from carbon black, carbon fiber, carbon nanotube, graphene, acetylene black, ketjen black, metal fiber, metal powder and conductive metal oxide. Preferred conductive additives include carbon black and carbon nanotube.

[0340] The one or more conductive additives may suitably be present in a total amount of 0.5 to 20 wt%, preferably 1 to 15 wt% and most preferably 2 to 10 wt%, based on the total dry weight of the electrode composition.

[0341] In a third aspect, the present invention provides an electrode comprising a granular material as defined in the first aspect of the present invention in electrical contact with a current collector. The granular material used to prepare the electrode of the third aspect of the present invention may have any of the features described as preferred or optional with respect to the first aspect of the present invention, and may be a granular material according to any one of aspects 1-1 to 1-41.

[0342] As used herein, the term current collector refers to any conductive substrate capable of carrying current to the electroactive particles in the electrode composition and carrying current out of the electroactive particles in the electrode composition. Examples of materials that can be used as current collectors include copper, aluminum, stainless steel, nickel, titanium and sintered carbon. Copper is a preferred material. The current collector is generally in the form of a foil or mesh having a thickness of 3 to 500 μm. The granular material of the present invention can be applied to one or both surfaces of the current collector to a thickness preferably in the range of 10 μm to 1 mm, for example 20 to 500 μm, or 50 to 200 μm.

[0343] Preferably, the electrode comprises an electrode composition as defined in accordance with the second aspect of the invention in electrical contact with a current collector.The electrode composition may have any of the features described as preferred or optional in relation to the second aspect of the invention.

[0344] The electrode of the third aspect of the present invention can be suitably prepared in the following manner: the granular material of the present invention (optionally in the form of an electrode composition of the present invention) is combined with a solvent and optionally one or more viscosity modifying additives to form a slurry. The slurry is then cast onto the surface of the current collector, and the solvent is removed to form an electrode layer on the surface of the current collector. Additional steps may be performed as appropriate, such as heat treatment for curing any binder and / or calendering of the electrode layer. The thickness of the electrode layer is suitably in the range of 20 μm to 2 mm, preferably 20 μm to 1 mm, preferably 20 μm to 500 μm, preferably 20 μm to 200 μm, preferably 20 μm to 100 μm, preferably 20 μm to 50 μm.

[0345] Alternatively, the slurry can be formed into a self-supporting film or mat comprising the particulate material of the present invention, for example by casting the slurry onto a suitable casting template, removing the solvent and then removing the casting template. The resulting film or mat is in the form of a cohesive, self-supporting object, which can then be combined with a current collector by known methods.

[0346] The electrode of the third aspect of the invention can be used as an anode of a metal ion battery. Therefore, in a fourth aspect, the invention provides a rechargeable metal ion battery comprising: an anode comprising an electrode as described above; a cathode comprising a cathode active material capable of releasing and reabsorbing metal ions; and an electrolyte between the anode and the cathode. The granular material used to prepare the battery of the fourth aspect of the invention may have any of the features described as preferred or optional with respect to the first aspect of the invention, and may be a granular material according to any one of aspects 1-1 to 1-41.

[0347] The metal ions are preferably lithium ions. More preferably, the rechargeable metal ion battery of the present invention is a lithium ion battery, and the cathode active material is capable of releasing and reabsorbing lithium ions.

[0348] The cathode active material is preferably a composite material based on metal oxides. Examples of suitable cathode active materials include LiCoO2, LiCo 0.99 Al 0.01 O2, LiNiO2, LiMnO2, LiCo 0.5 Ni 0.5 O2、LiCo 0.7 Ni 0.3 O2、LiCo 0.8 Ni 0.2 O2、LiCo 0.82 Ni 0.18 O2、LiCo 0.8 Ni 0.15 Al 0.05 O2、LiNi 0.4 Co 0.3 Mn 0.3 O2 and LiNi 0.33 Co 0.33 Mn 0.34 O2. The cathode current collector generally has a thickness of 3 to 500 μm. Examples of materials that can be used as the cathode current collector include aluminum, stainless steel, nickel, titanium, and sintered carbon.

[0349] Electrolyte is suitably a non-aqueous electrolyte containing a metal salt (e.g., a lithium salt), and may include, but is not limited to, a non-aqueous electrolyte, a solid electrolyte, and an inorganic solid electrolyte. Examples of usable non-aqueous electrolyte solutions include aprotic organic solvents, such as propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, sulfolane, methyl sulfolane, and 1,3-dimethyl-2-imidazolidinone.

[0350] Examples of the organic solid electrolyte include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ion dissociative groups.

[0351] Examples of inorganic solid electrolytes include nitrides, halides, and sulfides of lithium salts (such as Li5NI2, Li3N, LiI, LiSiO4, Li2SiS3, Li4SiO4, LiOH, and Li3PO4).

[0352] The lithium salt is suitably soluble in the selected solvent or solvent mixture. Examples of suitable lithium salts include LiCl, LiBr, LiI, LiClO4, LiBF4, LiBC4O8, LiPF6, LiCF3SO3, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li and CF3SO3Li.

[0353] In the case where the electrolyte is a non-aqueous organic solution, the metal ion battery preferably has a separator between the anode and the cathode. The separator is generally formed of an insulating material with high ion permeability and high mechanical strength. The separator generally has a pore size of 0.01 to 100 μm and a thickness of 5 to 300 μm. Examples of suitable electrode separators include microporous polyethylene films.

[0354] The separator may be replaced by a polymer electrolyte material, and in such a case, the polymer electrolyte material is present in both the composite anode layer and the composite cathode layer. The polymer electrolyte material may be a solid polymer electrolyte or a gel-type polymer electrolyte.

[0355] In a fifth aspect, the present invention provides the use of a particulate material as defined in accordance with the first aspect of the present invention as an anode active material. Preferably, the particulate material is in the form of an electrode composition as defined in accordance with the second aspect of the present invention, and most preferably, the electrode composition comprises one or more additional particulate electroactive materials as defined above. The particulate material used in accordance with the fifth aspect of the present invention may have any of the features described as preferred or optional with respect to the first aspect of the present invention, and may be a particulate material according to any one of aspects 1-1 to 1-41. BRIEF DESCRIPTION OF THE DRAWINGS

[0356] Figure 1 The graph shows the capacity retention rate of the battery in the example over multiple cycles. DETAILED DESCRIPTION

[0357] Example

[0358] The porous carbon frameworks C1 to C3 used in the following examples have the properties listed in Table 1.

[0359] Table 1

[0360]

[0361] Example 1 - Preparation of composite particles in a fixed bed reactor

[0362] Silicon-carbon composite particles are prepared by placing 1.8g of a porous skeleton of particles with the properties listed in Table 1 on a stainless steel plate with a constant thickness of 1mm along the length of the stainless steel plate. The plate is then placed in a stainless steel tube with an outer diameter of 60mm in the hot zone of a retort furnace, which has a gas inlet and outlet pipeline. The furnace tube is purged with nitrogen for 30 minutes at room temperature, and then the sample temperature is raised to 450-500°C. The nitrogen flow rate is adjusted to ensure a gas residence time of at least 90 seconds in the furnace tube, and the nitrogen flow rate is maintained at this rate for 30 minutes. Then, the gas supply is switched from nitrogen to a mixture of monosilane in nitrogen (the concentration of monosilane is 1.25 volume %). The feeding of monosilane is carried out in a period of 5 hours when the reactor pressure is maintained at 101.3kPa (1atm). After the feeding is completed, the gas flow rate is kept constant while purging silane from the furnace with nitrogen. The furnace is purged under nitrogen for 30 minutes and then cooled to room temperature within a few hours. The atmosphere was then gradually switched to air over a two hour period by switching the gas flow from nitrogen to air from a compressed air supply.

[0363] The composite material prepared according to Example 1 has the properties listed in Table 2 below.

[0364] Example 2 - Preparation of composite particles in a fluidized bed reactor

[0365] Silicon-carbon composite particles are prepared in a vertical bubbling fluidized bed reactor including a stainless steel cylindrical container with an inner diameter of 83mm. A 250g amount of carbon skeleton particle powder with the properties listed in Table 1 is placed in the reactor. An inert gas (nitrogen) with a low flow rate is injected into the reactor to remove all oxygen. The reactor is then heated to a reaction temperature of 400 to 500°C, and 4% v / v of monosilane gas diluted with nitrogen is supplied to the bottom of the reactor at a flow rate sufficient to sulfidize the carbon skeleton particles, for a duration sufficient to deposit the target mass of silicon. The reactor is purged under nitrogen for 30 minutes and then cooled to room temperature within a few hours. The atmosphere is then gradually switched to air over a two-hour period by switching the gas flow from nitrogen to air from a compressed air supply.

[0366] The composite material prepared according to Example 2 has the properties listed in Table 2 below.

[0367] Example 3 - Preparation of composite particles in a rotary tube furnace reactor

[0368] Silicon-carbon composite particles are prepared by placing 5 g of a porous skeleton of particles having the properties listed in Table 1 into a quartz tube with a bubble-shaped portion (11.4 cm long). The quartz tube is then placed inside a rotary reactor tube furnace having a heating zone of about 15 x 20 cm (L x D), and a gas inlet and outlet pipeline located about 29 cm from the hot zone of the furnace. The quartz tube in the furnace rotates clockwise by about 315 ° and then counterclockwise to continuously move / rotate the porous carbon. The furnace tube is purged with nitrogen for 30 minutes at room temperature, and then the sample temperature is raised to 450-500 ° C. The nitrogen flow rate is adjusted to ensure a gas residence time of at least 90 seconds in the furnace tube, and the nitrogen flow rate is maintained at this rate for 30 minutes. Then, the gas supply is switched from nitrogen to a mixture of 1.25 volume % concentration of monosilane in nitrogen. The feeding of monosilane was carried out over a period of 5 hours with the reactor pressure maintained at 101.3 kPa (1 atm). After the feeding was completed, the gas flow rate was kept constant while purging the silane from the furnace with nitrogen. The furnace was purged under nitrogen for 30 minutes and then cooled to room temperature over a period of several hours. The atmosphere was then gradually switched to air over a period of two hours by switching the gas flow from nitrogen to air from a compressed air supply.

[0369] The composite material prepared according to Example 3 has the properties listed in Table 2 below.

[0370]

[0371] Example 4 - Preparation of electrodes

[0372] Negative electrode coatings (anodes) were prepared from the materials of the samples and comparative samples given in Table 1 using the following method.

[0373] The test button cells were prepared using the negative electrode comprising the silicon-based composite material prepared as described above. (Conductive carbon) dispersion in CMC binder in Thinky TM The Si-C composite material was added to the mixture and mixed in a Thinky TM The mixture was mixed in a mixer for 30 min. SBR binder was then added to provide a CMC:SBR ratio of 1:1 to obtain a slurry with a weight ratio of Si-C composite material: CMC / SBR: carbon black of 70%:16%:14%. The slurry was placed in a Thinky TM The mixture was mixed in a mixer for another 30 minutes, and then coated onto a 10 μm thick copper substrate (current collector) and dried at 50° C. for 10 minutes and then at 110° C. for 12 hours, thereby forming a negative electrode.

[0374] Example 5 - Full Cell Fabrication

[0375] A full button cell was prepared using a circular negative electrode with a radius of 0.8 cm cut from the electrode of Example 4 with a porous polyethylene separator and a nickel manganese cobalt (NMC532) positive electrode. The positive and negative electrodes were designed to form a balanced pair so that the capacity ratio of the positive electrode to the negative electrode was 0.9. An electrolyte was then added to the cell before sealing, comprising 1M LiPF6 in a 7:3 solution of EMC / FEC (ethyl methyl carbonate / fluoroethylene carbonate) containing 3 wt% ethylene carbonate.

[0376] The full button cell was cycled as follows: a constant current was applied at a rate of C / 25 to lithiate the anode with a cutoff voltage of 4.3V. When the cutoff was reached, a constant voltage of 4.3V was applied until a cutoff current of C / 100 was reached. The cell was then left standing for 10 minutes in the lithiated state. The anode was then delithiated at a constant current of C / 25 with a cutoff voltage of 2.75V. The cell was then left standing for 10 minutes. After this initial cycle, a constant current of C / 2 was applied to lithiate the anode with a cutoff voltage of 4.3V, followed by a constant voltage of 4.3V with a cutoff current of C / 40 and a standing time of 5 minutes. The anode was then delithiated at a constant current of C / 2 with a cutoff of 2.75V. This process was then repeated for the desired number of cycles. The charge and discharge capacities were tracked until 1000 cycles, and the capacity retention (CR100 and CR300) of each sample at 100 and 300 cycles was determined. In the case of S1, S2 and S3, CR500 and CR1000 were also determined. This data is provided in Table 3 along with the 1st lithiation capacity, 1st delithiation capacity and first cycle loss (FCL) for each sample. Figure 1 The capacity retention rate over multiple cycles is shown in the figure.

[0377] The charge (lithiation) and discharge (delithiation) capacities per unit mass of the silicon-carbon composite material for each cycle were calculated, and the capacity retention value for each discharge capacity was calculated as a percentage of the discharge capacity of the second cycle. The first cycle loss (FCL) is (1–(1st delithiation capacity / 1st lithiation capacity))×100%. The values ​​in Table 3 are the averages of 3 button cells for each sample.

[0378] Table 3

[0379]

Claims

1. A granular material comprising a plurality of composite particles, wherein the composite particles comprise: (a) A porous carbon framework comprising micropores and mesopores, wherein (i) In the absence of silicon or any other material occupying the pores of the porous carbon framework, the total pore volume of the micropores and mesopores is P1 cm 3 / g, wherein P1 represents a dimensionless number with a value in the range of 0.6 to 0.9, wherein the total pore volume of the micropores and mesopores is calculated by nitrogen adsorption at 77 K down to 10 -6 The relative pressure p / p0 is measured using the density functional theory of quenched solids. (ii) Based on the total volume of micropores and mesopores, the volume fraction of micropores (φ a ) is in the range of 0.5 to 0.8; (iii) the volume fraction of pores having a pore diameter of not more than 5 nm (φ5) is at least 0.75 based on the total volume of micropores and mesopores, and (iv) D of the porous carbon skeleton 50 Particle size less than 20 µm; (b) a plurality of nano-sized elemental silicon domains located within the micropores and / or mesopores of the porous carbon framework; The weight ratio of silicon in the composite particles to the porous carbon skeleton is in the range of [1×P1 to 2.2×P1]:

1.

2. A particulate material according to claim 1, wherein the value of P1 is at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.

85.

3. The particulate material of claim 1, wherein the volume fraction of micropores is in the range of 0.55 to 0.8, or in the range of 0.6 to 0.8, or in the range of 0.6 to 0.75, based on the total volume of micropores and mesopores.

4. The granular material according to claim 1, wherein the volume fraction of micropores (φ a ) is in the range of 0.5 to 0.75, or in the range of 0.5 to 0.

7.

5. The granular material of claim 1, wherein the weight ratio of silicon in the composite particles to the porous carbon skeleton is at least [φ b +0.75]×P1, where φ b represents the volume fraction of mesopores based on the total volume of micropores and mesopores.

6. The granular material of claim 5, wherein the weight ratio of silicon in the composite particles to the porous carbon skeleton is at least [φ b +1] × the value given by P1.

7. The granular material of claim 6, wherein the weight ratio of silicon in the composite particles to the porous carbon skeleton is at least [φ b +1.1] × the value given by P1.

8. The granular material of claim 5, wherein the weight ratio of silicon in the composite particles to the porous carbon skeleton is no more than [φ b +1.6] × the value given by P1.

9. The granular material of claim 5, wherein the weight ratio of silicon in the composite particles to the porous carbon skeleton is no more than [φ b +1.5] × the value given by P1.

10. The particulate material of claim 3, wherein the weight ratio of silicon in the composite particles to the porous carbon skeleton is at least 1.1×P1, or at least 1.15×P1, or at least 1.2×P1, or at least 1.25×P1, or at least 1.3×P1, or at least 1.35×P1, or at least 1.4×P1.

11. The granular material according to claim 1, wherein the volume fraction of pores having a pore diameter of not more than 20 nm (φ 20 ) is at least 0.8, or at least 0.85, or at least 0.

9.

12. The granular material according to claim 1, wherein the volume fraction of pores having a pore diameter of not more than 10 nm (φ 10 ) is at least 0.8, or at least 0.

85.

13. The particulate material of claim 1, wherein the volume fraction of pores having a pore diameter of not more than 5 nm (φ5) is at least 0.8, or at least 0.85, based on the total volume of micropores and mesopores.

14. The particulate material of claim 1, wherein the porous carbon framework has a unimodal pore size distribution, wherein the pore size distribution represents the distribution of pore sizes of the porous carbon framework relative to the cumulative total internal pore volume.

15. The particulate material of claim 1, wherein the porous carbon framework has a bimodal or multimodal pore size distribution, wherein the pore size distribution represents the distribution of pore sizes of the porous carbon framework relative to the cumulative total internal pore volume.

16. The particulate material of claim 1, wherein the porous carbon framework comprises macropores with diameters ranging from greater than 50 nm to 100 nm, the total volume of the macropores as measured by mercury intrusion porosimetry being P2 cm 3 / g, wherein P2 does not exceed 0.2×P1, or does not exceed 0.1×P1, or does not exceed 0.05×P1, or does not exceed 0.02×P1, or does not exceed 0.01×P1, or does not exceed 0.005×P1.

17. The granular material of claim 1, wherein the D of the composite particles 50 The particle size is at least 0.5 µm, at least 1 µm, or at least 2 µm, or at least 3 µm, or at least 4 µm, or at least 5 µm.

18. The granular material of claim 1, wherein the D of the composite particles 50 Particle size not exceeding 18 µm, or not exceeding 16 µm, or not exceeding 14 µm, or not exceeding 12 µm, or not exceeding 10 µm, or not exceeding 9 µm, or not exceeding 8 µm, or not exceeding 7 µm, or not exceeding 6 µm, or not exceeding 5 µm.

19. The granular material of claim 1, wherein the D of the composite particles 10 The particle size is at least 0.2 µm, or at least 0.5 µm, or at least 0.8 µm, or at least 1 µm, or at least 1.5 µm, or at least 2 µm.

20. The granular material of claim 1, wherein the D of the composite particles 90 Particle size not exceeding 40 µm, or not exceeding 30 µm, or not exceeding 20 µm, or not exceeding 15 µm, or not exceeding 12 µm, or not exceeding 10 µm.

21. The particulate material of claim 1, wherein the composite particles have a particle size distribution span of 5 or less, or 4 or less, or 3 or less, or 2 or less, or 1.5 or less, wherein the particle size distribution span is defined as (D 90 -D 10 ) / D 50 .

22. The particulate material of claim 1, wherein the composite particles have a BET surface area of ​​no more than 150 m 2 / g, or not more than 100 m 2 / g, or not more than 80 m 2 / g, or not more than 60 m 2 / g, or not more than 40 m 2 / g, or not more than 30 m 2 / g, or not more than 25 m 2 / g, or not more than 20 m 2 / g, or not more than 15 m 2 / g.

23. The particulate material of claim 1, wherein the composite particles have a BET surface area of ​​at least 0.1 m 2 / g, or at least 1 m 2 / g, or at least 2 m 2 / g, or at least 5 m 2 / g.

24. The particulate material of claim 1, having a lithiation specific capacity of 1200 to 2340 mAh / g.

25. The particulate material of claim 1, wherein at least 90 weight percent of the mass of silicon in the composite particles is located within the internal pore volume of the porous carbon framework.

26. The particulate material of claim 1, wherein no more than 10% of the silicon content in the particulate material is unoxidized at 800°C when the particulate material is analyzed by TGA in air at a heating rate of 10°C / min, wherein the percentage of silicon that is unoxidized at 800°C is determined according to the formula: Z = 1.875 × [(M f - M 800 ) / M f ] ×100% Where Z is the percentage of silicon that is not oxidized at 800°C, M f is the mass of the sample at the completion of oxidation, and M 800 is the mass of the sample at 800 °C.

27. A particulate material according to claim 26, wherein no more than 5% of the silicon content in the particulate material is unoxidised at 800°C when the particulate material is analysed by TGA in air at a heating rate of 10°C / min.

28. A particulate material according to claim 27, wherein no more than 2% of the silicon content in the particulate material is unoxidised at 800°C when the particulate material is analysed by TGA in air at a heating rate of 10°C / min.

29. A composition comprising a particulate material as defined in any one of claims 1 to 28 and at least one other component.

30. A composition according to claim 29, comprising a particulate material as defined in any one of claims 1 to 28 and at least one further component selected from: (i) a binder; (ii) a conductive additive; and (iii) a further particulate electroactive material.

31. A composition according to claim 30 comprising at least one additional particulate electroactive material.

32. A composition according to claim 31 comprising from 1 to 20 wt%, or from 2 to 15 wt%, or from 2 to 10 wt% or from 2 to 5 wt% of the particulate material as defined in any one of claims 1 to 28, based on the total dry weight of the composition.

33. A composition according to claim 31 comprising 10 to 98 wt%, or 15 to 97 wt%, or 20 to 97 wt% or 25 to 97 wt% of the at least one additional particulate electroactive material based on the total dry weight of the composition.

34. The composition of claim 31 , wherein the at least one additional particulate electroactive material has a specific lithiation capacity in the range of 100 to 600 mAh / g or 200 to 500 mAh / g.

35. The composition of claim 31 , wherein the at least one additional particulate electroactive material is selected from graphite and hard carbon.

36. The composition of claim 30, comprising a binder in an amount of 0.5 to 20 wt%, or 1 to 15 wt%, or 2 to 10 wt%, based on the total dry weight of the composition.

37. The composition of claim 30, comprising one or more conductive additives in a total amount of 0.5 to 20 wt%, or 1 to 15 wt%, or 2 to 10 wt%, based on the total dry weight of the composition.

38. An electrode comprising a particulate material as defined in any one of claims 1 to 28 in electrical contact with a current collector.

39. An electrode according to claim 38, wherein the particulate material is in the form of a composition as defined in any one of claims 29 to 37.

40. A rechargeable metal ion battery, comprising: (i) an anode, wherein the anode comprises an electrode as claimed in claim 38 or claim 39; (ii) a cathode comprising a cathode active material capable of releasing and reabsorbing metal ions; and (iii) an electrolyte between the anode and the cathode.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2003100284A

  • A method of fabricating fibres composed of silicon or a silicon-based material and their use in lithium rechargeable batteries

    WO2007083155A1

  • Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof

    US20170170477A1

  • Decomposition of silicon-containing precursors on porous scaffold materials

    WO2018165610A1